2013
DOI: 10.1093/nar/gkt585
|View full text |Cite
|
Sign up to set email alerts
|

DHX34 and NBAS form part of an autoregulatory NMD circuit that regulates endogenous RNA targets in human cells, zebrafish and Caenorhabditis elegans

Abstract: The nonsense-mediated mRNA decay (NMD) pathway selectively degrades mRNAs harboring premature termination codons but also regulates the abundance of cellular RNAs. We sought to identify transcripts that are regulated by two novel NMD factors, DHX34 and neuroblastoma amplified sequence (NBAS), which were identified in a genome-wide RNA interference screen in Caenorhabditis elegans and later shown to mediate NMD in vertebrates. We performed microarray expression profile analysis in human cells, zebrafish embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 67 publications
4
107
1
Order By: Relevance
“…These studies point to a feedback loop where components of the NMD machinery are also regulated by the pathway (34). The regulation of NMD factors by the pathway has also been observed in zebrafish and C. elegans, further supporting the notion of a conserved NMD feedback loop (74).…”
Section: Atypically Long 3= Utrs Can Target Mrnas To the Nmd Pathwaysupporting
confidence: 55%
“…These studies point to a feedback loop where components of the NMD machinery are also regulated by the pathway (34). The regulation of NMD factors by the pathway has also been observed in zebrafish and C. elegans, further supporting the notion of a conserved NMD feedback loop (74).…”
Section: Atypically Long 3= Utrs Can Target Mrnas To the Nmd Pathwaysupporting
confidence: 55%
“…Therefore the situation appears analogous to what occurs in higher eukaryotes in which such introns can trigger EJC-mediated NMD. NMD control of N. crassa upf1 mRNA stability might be exerted through recognition of its uORF stop codons as PTCs, as is the case for N. crassa arg-2 ( Figure 5A) and S. cerevisiae CPA1 (Gaba et al 2005), or through its relatively long 39-UTR ( Figure 1A) as is reported for metazoan UPF1 (Huang et al 2011;Longman et al 2013), but this remains to be determined.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore the situation appears analogous to what occurs in higher eukaryotes in which such introns can trigger EJC-mediated NMD. NMD control of N. crassa upf1 mRNA stability might be exerted through recognition of its uORF stop codons as PTCs, as is the case for N. crassa arg-2 ( Figure 5A) and S. cerevisiae CPA1 (Gaba et al 2005), or through its relatively long 39-UTR ( Figure 1A) as is reported for metazoan UPF1 (Huang et al 2011;Longman et al 2013), but this remains to be determined.To our knowledge, this work represents the first demonstration of circuits that enables regulation at the level of mRNA stability for eRF1, eIF4a3, and Y14. Autoregulation of mRNA levels for NMD factors has been reported for metazoans (Huang et al 2011;Yepiskoposyan et al 2011; reviewed in Karam et al 2013;Longman et al 2013) and autoregulation of NMD and EJC factors has been reported for plants (Nyiko et al 2013).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Figure 4 depicts the molecular architecture of the core NMD factors and summarizes their functions and interaction sites, both of which are discussed in detail below. A number of additional NMD factors have been identified in different organisms, including SMG8, SMG9, PNRC2, DHX34, NBAS, RUVBL1, RUVBL2, MOV10, GNL2 and SEC13 for the human system [107][108][109][110][111][112][113].…”
Section: Nmd Factors and Their Role In Substrate Recognition And Degrmentioning
confidence: 99%